Biodiversity and Microbial Resistance of Lactobacilli Isolated From the Traditional Greek Cheese Kopanisti - Rozos, Georgios; Voidarou, Chrysa; Stavropoulou, Elisavet; Skoufos, Ioannis; Tzora, Athina; Alexopoulos, Athanasios; Bezirtzoglou, Eugenia (Frontiers in Microbiology, 2018)
Kopanisti is a Greek artisan cheese produced from raw milk in the island of Mykonos, Greece. The milk is left to rest for 12-24 hours and then the rennet is added. After its formation the curd is left to drain for 2-3 days and is ready either for consumption (as tyrovolia fresh cheese), or with the addition of extra salt, the curd is left to ripen through further fermentation and surface development of Penicillium fungi, aprocess leading to the production of the traditional Greek cheese Kopanisti. From 120 samples of kopanisti, 574 Lactobacillus strains were isolated, distributed in 17 species (16 of them isolated from tyrovolia as well). Strains from 15 species were found resistant or multiresistant against 15 antimicrobial agents, representing all categories of antibiotics. Analysis revealed that the resistance was moderated during ripening of the curd from tyrovolia to Kopanisti. Resistance against penicillin G, ampicillin/sulbactam, clindamycin, chloramphenicol, streptomycin, trimethoprim, metronidazole, vancomycin, teichoplanin and quinupristin/dalvopristin was significantly enhanced, while the resistance against ampicillin, erythromycin, oxytetracycline, gentamycin and fucidic acid was significantly reduced. These changes during ripening suggest that resistance to antimicrobials is a dynamic process subjected to environmental factors. The biodiversity of isolated Lactobacillus strains is impressive and explains the exquisite sensorial characteristics of the cheese. However the extent of the resistance is alarming.